PENGARUH PERILAKU WAJIB PAJAK TERHADAP PENGGUNAAN E-FILLING (Students' Journal of Accounting and Banking, 2014)
This study aimed to examine the effect of perceived usefulness, Perceived ease of use, attitude toward using, Perceived usefully, User satisfaction of the User E-fillimg. The research method used in this research is descriptive associative method, sampling using convenience samplingand analysis used is multiple regression. Regression analysis showed that the perceived usefulness, Perceived ease of use, attitude toward using, Perceived Usefully does not have a significant effect on Use E-filling, while User satisfaction significantly affecton UserE-filling. Keywords: Perceived Usefulness, Perceived Ease of Use, Attitude Toward Using, Perceived Usefully, UserSatisfaction of the User E-filling